Spawning and growth of three species of threadfin breams off Madras - Vivekanandan, E (Indian Journal of Fisheries, 2011)
Considering the impcmtuice of threadfinl»«ams, Vivdcan&nilui and Junes (1986) studiedthe spawning, growth »id peculation dymunicsotNemiptermjaponicus in the trawluiggrounds off Madras. As a continuation ofthis study, the owning and growth of 3 otherqxciesof dueadfln breams, viz.M mesoprion(Bleek^), N. tolu (Valenciennes) and N.delagoae Smith, were studied. The resultsobained during the study are presented inthis paper.